The Endothelial Glycocalyx as a Double-Edged Sword in Microvascular Homeostasis and Pathogenesis - Villalba, Nuria; Baby, Sheon; Yuan, Sarah Y. (Frontiers in Cell and Developmental Biology, 2021)
Expressed on the endothelial cell (EC) surface of blood vessels, the glycocalyx (GCX), a thin mixture of carbohydrates attached to proteins, regulates the access of cells and molecules in the blood to the endothelium. Besides protecting endothelial barrier integrity, the dynamic microstructure of the GCX confers remarkable functions including mechanotransduction and control of vascular tone. Recently, a novel perspective has emerged supporting the pleiotropic roles of the endothelial GCX in cardiovascular health and disease. Because GCX degradation occurs in certain pathological states, the circulating levels of GCX degradation products have been recognized to have diagnostic or prognostic values. Beyond their biomarker roles, certain GCX fragments serve as pathogenic factors in disease progression. Pharmacological interventions that attenuate GCX degradation or restore its integrity have been sought. This review provides our current understanding of GCX structure and function across the microvasculature in different organs. We also discuss disease or injury states, such as infection, sepsis and trauma, where GCX dysfunction contributes to severe inflammatory vasculopathy.